PENGARUH SERTIFIKASI HALAL TERHADAP RUMAH POTONG HEWAN (RPH) - Nurfa, Nurfa; Gustina, Gustina; Jum'an, Jum'an; Nurhakim, Lukman (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to determine the effect of halal certification on slaughterhouses is a building or complex of buildings specifically designed to meet certain technical and hygienic requirements and is also used for slaughtering animals using descriptive qualitative research methods. Halal certification is a process where halal certification is obtained through several inspection steps to prove that the raw materials, production process and halal product guarantee system of the Company have met the established standards. According to the Regulation of the Minister of Agriculture Number 13 paragraph (1) number 2 of 2010, in terms of Ruminant Slaughterhouses and Meat, a Slaughterhouse, hereinafter abbreviated as RPH, is a building or complex of buildings that are treated as slaughterhouses. . The establishment of a Halal system must meet the criteria of the HAS 23000 Halal Assurance system. To accelerate the Halal certification process, the government has taken the Halal Product Guarantee (JPH) policy which is a derivative of the Job Creation Law Number 11 of 2020. Based on PP article 140 no. Article 39 of the Halal Product Guarantee in 2021 states that the determination of halal certification guarantees for food, beverages, slaughter products, and slaughter services will be carried out in stages. Slaughter products are the most important ingredient and slaughterhouses are at the top of the production chain, so slaughterhouses must ensure that the slaughter and processing process is carried out in accordance with Islamic law and established halal rules. If the meat produced in the slaughterhouse is not halal, then the meat products and processed products are also non-halal products. Based on these three standards, abattoirs can produce good products while reducing adverse impacts on the environment. Meat must be slaughtered in a slaughterhouse in such a way that it is halal, safe and healthy. Meat slaughtering consists of several stages: receiving cattle, protection, pre-slaughter inspection, inspection of productive females, slaughtering and inspection